Prodigality, liberality and meanness in the parable of the prodigal son : Greco-Roman perspective on Luke 15:11-32 - Holgate, David A (Rhodes University, Faculty of Divinity, Department of Divinity, 1993)
This dissertation consists of an interpretation of the Parable of the Prodigal Son (Luke 15: 11-32) from the perspective of Greco-Roman moral philosophy. It is divided into three parts. Part 1 traces the history of relating the New Testament to Greco-Roman literature and philosophy. Despite the importance of this perspective for the study of Luke-Acts, the relationship between Luke 15: 11-32 and Greco-Roman moral philosophy has not been investigated before. The legitimacy of this approach is demonstrated by a literary analysis of the parable, which demonstrates the formal emphasis placed upon the liberal and compassionate words and actions of the father. The strong moral orientation of the parable is further illustrated by the formal, linguistic and thematic features which it shares with the other L parables. Part 2 consists of a study of the Greco-Roman moral topos On Covetousness. The use of the Greco-Roman topos as a critical tool for the study of the New Testament is evaluated, the term is defined, and the influence of the topos On Covetousness upon representative works of moral philosophy is studied. This part ends with a summary of the characteristic features of the topos and its use by writers with differing philosophical affiliations. Part 3 reads the whole parable in terms of the topos On Covetousness,with the emphasis being placed on the relationship between the Lukan text and works of Greco-Roman moral philosophy. The parable is seen to be structured according to the influential Peripatetic doctrine of the mean, with the father representing the virtue of liberality, and his two sons the opposing vices of prodigality and meanness. The comparison with the topos reveals Luke's strong rejection of the two vices, and his endorsement of the Greco-Roman virtue of liberality, which is modified by his emphasis upon the Christian virtue of compassion. The approach affirms and demonstrates the internal unity of the parable and its close relationship to the Lukan theme of the correct use of possessions.
Keywords: Bible. Luke XV, 11-32 -- Criticism, interpretation, etc.; Prodigal son (Parable); Ethics in the Bible